ANTICOCCIDIAL EFFECTS OF CALOTROPIS PROCERA POWDER ON COCCIDIOSIS OF RABBITS IN STATIONARY REARING - ADENILE, DOUROSSIMI ADAM; ANAGONOU, SESSIWEDE INGRID NADINE; ADEHAN, SAFIOU BIENVENU (My University, 2023)
The problem of diarrhea in rabbit farms is a major concern for breeders, who are often powerless to deal with this plague. Diarrhea and coccidiosis are two diseases in rabbits that are very much feared by breeders because they lead to high mortality in young rabbits, which can reach 90 to 100% of the population. The present study mainly aims to valorize medicinal plants at a lower cost in the farms and to contribute to the improvement of rabbit farming practices in Benin. Our study allowed, with the help of the extraction of the latex extract, to obtain from a volume of 42 cl of latex, a total weight of 396 g of Calotropis procera extract with a yield of 31.42%. Coprological analyses to establish lots of infested animals resulted in a 90% rate of infested animals. With infestation intensities varying between 500 and 6000 eggs per gram of excrement. The experimental treatment involved 100 rabbits, 25 of which were not infested, at doses of 0.5, 0.9, and 1.3 g of Calotropis procera extract per kg of body weight. The 0.5g/kg dose administered to the animals showed that at D4 the infested animals were not cured and 100% mortality rates were recorded in lots 2000 ≥ OPG < 5000 and OPG ≥ 5000. The 0.9g/kg dose induced a decrease in parasite load recorded at D4 in all lots with a mortality rate of 44% in all 25 animals receiving this dose and especially in lots 2000 ≥ OPG < 4000 and OPG ≥ 5000. The best therapeutic effects were obtained with the administration of dose d1.3 which induced a significant reduction (P < 0.05) in oocysts in all subjects at D5 with 4% mortality (p < 0.01). Depending on the determination of the toxic dose of Calotropis procera for rabbits, this plant with anticoccidial virtue may well be an alternative solution in the control of coccidiosis in rabbits. It could also slow down the reduction of zootechnical performances and the important mortality of rabbits (90 to 100% of the population) 11 induced by coccidiosis, which explains the considerable economic losses that it generates in this sector.
Keywords: Rabbits; Coccidiosis; Pulverulent; Calotropis procera; Benin